Investigation of cell‐free poly lactic acid/nanoclay scaffolds prepared via thermally induced phase separation technique containing hydroxyapatite nanocarriers of erythropoietin for bone tissue engineering applications. (19th October 2020) - Salehi, Majid; Bastami, Farshid; Rezai Rad, Maryam; Nokhbatolfoghahaei, Hanieh; Paknejad, Zahrasadat; Nazeman, Pantea; Hassani, Ali; Khojasteh, Arash
Abstract : The use of cell‐free scaffolds containing bioactive molecules having a controlled released pattern has been proposed as a promising approach in field of tissue engineering. This system would eliminate the challenges associated with cell implantation. For bone tissue engineering, in particular, the environment in favor of both de novo bone formation and vascularization are considered critical approach. Erythropoietin (EPO) has been shown to have bone‐related pleiotropic effects. However, due to the adverse systemic side effect, its local administration with controlled release has been recommended. This study aimed to fabricate erythropoietin (EPO)‐releasing poly lactic acid (PLA)/nanoclay (NC)/nanohydroxyaptitite (nHA) as a new scaffold for bone tissue engineering application. PLA/NC/nHA‐EPO scaffolds were fabricated using thermally induced phase separation technique. The fabricated scaffolds were first characterized in terms of morphology and physical properties, as well as their EPO realizing pattern. Then, their biocompatibility was assessed in response to the MG‐63 human osteoblast‐like cell line. Finally, its bone regeneration capability was evaluated in a rat calvarial model. The result showed that the fabricated scaffolds presented acceptable physical properties with the sustained release of EPO. The in vitro biocompatibility was also approved. Their bone regeneration in rat calvaria showed that the PLA/NC/nHA‐EPO scaffolds were significantly able to generate bone formation (41% after 8 weeks). Also, the formation of new vessels and capillaries were evident. The presence of osteoblast in the defect also confirmed that the EPO was potent in inducing mesenchymal stem cells chemotaxis. The PLA/NC/nHA containing EPO could be a promising cell‐free bioscaffold for bone tissue regeneration.